High-strength high-conductivity rare earth copper-tin alloy and preparation method thereof
Patent Information
- Application Number
- CN202410136058.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-31
AI Technical Summary
[0004]为了解决目前Cu-Ni-Sn系合金强度不足和导电率低问题,本发明提供了一种高强高导稀土铜锡合金及其制备方法,通过向合金中添加Zn、Ti和稀土元素Y,实现了提高铜合金强度的同时提高导电率
[0016]本发明中Zn元素的添加显著影响合金的机械性能,有利于提高合金的屈服强度、极限抗拉强度和伸长率。合金中添加Ti元素可以细化晶粒,并提高合金抗蠕变性能,提高合金的再结晶温度,使合金在高温环境下具有更优异的性能。合金冷轧变形处理后发生严重塑性变形,强化铜基体。添加稀土元素Y促进再结晶过程中形成细小再结晶晶粒,提高合金强度。因此,本发明具有制备过程简单,工艺流程短、高强度、高导电性、热加工性能优良等特点。
Smart Images

Figure CN118147482B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of copper alloy materials technology, and specifically relates to a high-strength, high-conductivity rare-earth copper-tin alloy and its preparation method. Background Technology
[0002] Cu-Ni-Sn alloys, with their high strength, high conductivity, and excellent corrosion resistance, have become key materials for manufacturing high-end instruments and electronic components. Cu-Ni-Sn alloys can overcome the shortcomings of traditional Cu-Be alloys, exhibiting higher thermal stability, high-temperature strength, and resistance to high-temperature stress relaxation. Furthermore, their production process does not emit toxic gases, making them a popular environmentally friendly material. Since the advent of leadframes in the 1960s, Cu-Ni-Sn alloys have become the primary material for leadframes due to their superior strength and conductivity.
[0003] With the continuous development of fields such as electronic circuits, aerospace, and mechanical engineering, the demand for high-performance copper alloy materials is gradually increasing. Currently, Cu-Ni-Sn alloys still face problems of insufficient strength and low conductivity. Therefore, it is urgent to research and develop copper alloys with superior performance to meet the development requirements of related fields. Existing technology, "A High-Strength Copper Alloy and Its Preparation Method" (Application Publication No. CN 114645155A), discloses that adding at least one element from Co, Ti, and Y can improve the strength of Cu-Ni-Sn. Existing technology, "A High-Strength, High-Elasticity Cu-Ni-Sn Alloy with High-Temperature Softening Resistance and Its Preparation Method" (Application Publication No. CN 114086027 A), discloses that Zn makes a significant contribution to the mechanical properties and high-temperature softening resistance of Cu-Ni-Sn alloys. Summary of the Invention
[0004] To address the issues of insufficient strength and low conductivity in current Cu-Ni-Sn alloys, this invention provides a high-strength, high-conductivity rare-earth copper-tin alloy and its preparation method. By adding Zn, Ti, and rare-earth element Y to the alloy, the strength of the copper alloy is improved while its conductivity is also increased.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0006] This invention provides a high-strength, high-conductivity rare-earth copper-tin alloy. By weight percentage, the alloy raw material composition is: Sn: 1.8-2.1%, Ni: 0.8-1.0%, Zn: 0.4-0.6%, Ti: 0.2-0.3%, rare earth element Y: 0.1-0.2%, and the balance is Cu.
[0007] This invention also provides a method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy, comprising the following steps:
[0008] Step S1, Ingredient preparation: Prepare the ingredients according to the above alloy raw material composition;
[0009] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas is introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 0.5 to 1 hour, and naturally cooled to obtain Cu-45%Ti master alloy for later use.
[0010] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0011] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5 to 10:1.
[0012] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then water quenched.
[0013] Step S6, cold rolling: The alloy sample obtained in step S5 is subjected to cold rolling deformation, with a deformation amount of 60%.
[0014] Step S7, double aging treatment: aging temperature is 400℃~550℃, aging time is 10min~240min, and the alloy sample is cooled and then subjected to double aging treatment at the same temperature and time.
[0015] The present invention has the following beneficial effects:
[0016] The addition of Zn significantly affects the mechanical properties of the alloy, improving its yield strength, ultimate tensile strength, and elongation. The addition of Ti refines the grains, improves creep resistance, and increases the recrystallization temperature, resulting in superior performance at high temperatures. Severe plastic deformation occurs after cold rolling, strengthening the copper matrix. The addition of rare earth element Y promotes the formation of fine recrystallized grains during recrystallization, increasing the alloy's strength. Therefore, this invention features a simple preparation process, short process flow, high strength, high electrical conductivity, and excellent hot working properties.
[0017] Compared to the patent "A High-Strength Copper Alloy and Its Preparation Method" (Application Publication No. CN 114645155A), this invention improves the alloy's hardness, electrical conductivity, and tensile strength through secondary aging heat treatment. In the patent "A High-Strength, High-Elasticity Cu-Ni-Sn Alloy Resistant to High-Temperature Softening and Its Preparation Method" (Application Publication No. CN 114086027 A), the Ni content reaches 14–16 wt.%. The increased Ni content increases the solubility of hydrogen in the alloy, leading to severe hydrogen absorption and deterioration of alloy properties, requiring protective measures. Furthermore, the smelting process necessitates an upward continuous casting process. In contrast, the Ni content in this invention is only 0.8–1.0%, eliminating the need for hydrogen removal. Additionally, the smelting process is simple and has a short flow rate. Attached Figure Description
[0018] Figure 1 The microstructure of different regions of the rare earth copper-tin alloy prepared in this invention is shown. Detailed Implementation
[0019] The present invention will now be described in more detail through specific embodiments to facilitate understanding of the technical solution of the present invention, but this is not intended to limit the scope of protection of the present invention.
[0020] Example 1
[0021] A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy includes the following steps:
[0022] Step S1, Ingredients: The alloy raw materials are prepared according to the following composition by weight percentage: Sn: 2.0%, Ni: 1.0%, Zn: 0.5%, Ti: 0.25%, rare earth element Y: 0.15%, and the balance is Cu;
[0023] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 1 hour, and naturally cooled to obtain a Cu-45%Ti master alloy for later use.
[0024] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0025] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5:1.
[0026] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then water quenched.
[0027] Step S6, cold rolling: The alloy sample is cold-deformed with a deformation amount of 60%;
[0028] Step S7, Double aging treatment: The aging temperature is 500℃, and the aging time is 120 min. After the alloy sample cools, it undergoes a double aging treatment at the same temperature and time to obtain the Cu-Sn-Ni-Zn-Ti-Y alloy. The microstructure is shown in [see details]. Figure 1 ,Depend on Figure 1 It can be seen that a large number of nanoscale precipitates are formed in the alloy.
[0029] Example 2
[0030] A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy includes the following steps:
[0031] Step S1, Ingredients: The alloy raw materials are prepared according to the following composition by weight percentage: Sn: 1.8%, Ni: 1.0%, Zn: 0.5%, Ti: 0.25%, rare earth element Y: 0.15%, and the balance is Cu;
[0032] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 1 hour, and then naturally cooled to obtain a Cu-45%Ti master alloy for later use.
[0033] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0034] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5:1 to obtain bar billets;
[0035] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then water quenched.
[0036] Step S6, cold rolling: The alloy sample is cold rolled to deform it by 60%;
[0037] Step S7, double aging treatment: The aging temperature is 500℃ and the aging time is 120min. After the alloy sample is cooled, it is subjected to double aging treatment at the same temperature and time to obtain Cu-Sn-Ni-Zn-Ti-Y alloy.
[0038] Example 3
[0039] A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy includes the following steps:
[0040] Step S1, Ingredients: The alloy raw materials are prepared according to the following composition by weight percentage: Sn: 1.9%, Ni: 1.0%, Zn: 0.5%, Ti: 0.25%, rare earth element Y: 0.15%, and the balance is Cu;
[0041] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 1 hour, and then naturally cooled to obtain a Cu-45%Ti master alloy for later use.
[0042] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0043] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5:1.
[0044] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then water quenched.
[0045] Step S6, cold rolling: The alloy sample is cold rolled to deform it by 60%;
[0046] Step S7, double aging treatment: The aging temperature is 500℃ and the aging time is 120min. After the alloy sample is cooled, it is subjected to double aging treatment at the same temperature and time to obtain Cu-Sn-Ni-Zn-Ti-Y alloy.
[0047] Example 4
[0048] A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy includes the following steps:
[0049] Step S1, Batching: Batchute according to the following alloy raw material composition: Sn: 2.1%, Ni: 1.0%, Zn: 0.5%, Ti: 0.25%, rare earth element Y: 0.15%, balance Cu;
[0050] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 1 hour, and then naturally cooled to obtain a Cu-45%Ti master alloy for later use.
[0051] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0052] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5:1.
[0053] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then water quenched.
[0054] Step S6, cold rolling: The alloy sample is cold rolled to deform it by 60%;
[0055] Step S7, double aging treatment: The aging temperature is 500℃ and the aging time is 120min. After the alloy sample is cooled, it is subjected to double aging treatment at the same temperature and time to obtain Cu-Sn-Ni-Zn-Ti-Y alloy.
[0056] Example 5
[0057] A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy includes the following steps:
[0058] Step S1, Ingredients: The alloy raw materials are prepared according to the following composition by weight percentage: Sn: 2.0%, Ni: 1.0%, Zn: 0.5%, Ti: 0.15%, rare earth element Y: 0.15%, and the balance is Cu;
[0059] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 1 hour, and then naturally cooled to obtain a Cu-45%Ti master alloy for later use.
[0060] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0061] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5:1.
[0062] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then water quenched.
[0063] Step S6, cold rolling: The alloy sample is cold rolled to deform it by 60%;
[0064] Step S7, double aging treatment: The aging temperature is 500℃ and the aging time is 120min. After the alloy sample is cooled, a second aging treatment at the same temperature and time is performed to obtain the Cu-Sn-Ni-Zn-Ti-Y alloy.
[0065] Example 6
[0066] A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy includes the following steps:
[0067] Step S1, Ingredients: The alloy raw materials are prepared according to the following composition by weight percentage: Sn: 2.0%, Ni: 1.0%, Zn: 0.5%, Ti: 0.25%, rare earth element Y: 0.15%, and the balance is Cu;
[0068] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 1 hour, and then naturally cooled to obtain a Cu-45%Ti master alloy for later use.
[0069] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0070] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5:1.
[0071] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then water quenched.
[0072] Step S6, cold rolling: The alloy sample is cold rolled to deform it by 60%;
[0073] Step S7, single aging treatment: aging temperature is 500℃, aging time is 120min, and Cu-Sn-Ni-Zn-Ti-Y alloy can be obtained.
[0074] Example 7
[0075] A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy includes the following steps:
[0076] Step S1, Ingredients: The alloy raw materials are prepared according to the following composition by weight percentage: Sn: 2.0%, Ni: 1.0%, Zn: 0.5%, Ti: 0.25%, rare earth element Y: 0.15%, and the balance is Cu;
[0077] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 1 hour, and then naturally cooled to obtain a Cu-45%Ti master alloy for later use.
[0078] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0079] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5:1.
[0080] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then water quenched.
[0081] Step S6, cold rolling: The alloy sample is cold rolled to deform it by 60%;
[0082] Step S7, double aging treatment: The aging temperature is 450℃ and the aging time is 120min. After the alloy sample is cooled, a second aging treatment at the same temperature and time is performed to obtain the Cu-Sn-Ni-Zn-Ti-Y alloy.
[0083] Example 8
[0084] A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy includes the following steps:
[0085] Step S1, Ingredients: The alloy raw materials are prepared according to the following composition by weight percentage: Sn: 2.0%, Ni: 1.0%, Zn: 0.5%, Ti: 0.25%, rare earth element Y: 0.15%, and the balance is Cu;
[0086] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 1 hour, and then naturally cooled to obtain a Cu-45%Ti master alloy for later use.
[0087] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0088] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5:1.
[0089] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then the alloy is water quenched.
[0090] Step S6, cold rolling: The alloy sample is cold rolled to deform it by 60%;
[0091] Step S7, double aging treatment: The aging temperature is 550℃ and the aging time is 120min. After the alloy sample is cooled, it is subjected to double aging treatment at the same temperature and time to obtain Cu-Sn-Ni-Zn-Ti-Y alloy.
[0092] Example 9
[0093] A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy includes the following steps:
[0094] Step S1, Ingredients: The alloy raw materials are prepared according to the following composition by weight percentage: Sn: 2.0%, Ni: 1.0%, Zn: 0.5%, Ti: 0.25%, rare earth element Y: 0.15%, and the balance is Cu;
[0095] Step S2, Preparation of intermediate alloy: Copper and titanium are placed in a vacuum non-consumable arc melting furnace at a weight ratio of 20:9, and the furnace is evacuated to a pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa, heated to 1100℃, smelted for 1 hour, and then naturally cooled to obtain a Cu-45%Ti master alloy for later use.
[0096] Step S3: Melting, casting, and peeling; evacuate the vacuum induction furnace to a pressure of 5 × 10⁻⁶ molten metal. 2Pa, then argon gas was introduced into the furnace to a pressure of 0.05 MPa. The Cu-45%Ti master alloy, Sn, Ni, Zn, Y and the balance Cu were melted in a vacuum medium-frequency melting furnace to obtain an alloy melt. The melting temperature was 1200℃ and the melting time was 1 hour. The alloy melt was poured into a sand mold and cooled to obtain an alloy ingot. The riser of the alloy ingot was removed and the surface oxide scale was machined off.
[0097] Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5:1.
[0098] Step S5, solution treatment: The alloy bar obtained in step S4 is subjected to solution treatment. The alloy is heated to 950°C in a vacuum tube furnace and held for 2 hours, and then the alloy is water quenched.
[0099] Step S6, cold rolling: The alloy sample is cold rolled to deform it by 60%;
[0100] Step S7, double aging treatment: The aging temperature is 500℃ and the aging time is 60min. After the alloy sample is cooled, it is subjected to double aging treatment at the same temperature and time to obtain Cu-Sn-Ni-Zn-Ti-Y alloy.
[0101] The rare earth copper-tin alloy samples prepared in Examples 1 to 9 above were subjected to hardness testing, electrical conductivity testing, and tensile property testing.
[0102] The hardness of the alloy samples was determined using an HVS-1000 Vickers hardness tester with a load of 500g and a holding time of 10s. Ten points were taken from each sample to ensure data accuracy. The electrical conductivity of the alloy samples was tested using a Singa 2008B1 digital conductivity meter, and the tensile strength of the alloy samples was determined using an AG-I-250kN tensile tester. The results are shown in Table 1.
[0103] Table 1. Performance test results of alloys prepared in different embodiments
[0104]
[0105]
[0106] According to the test results in Table 1, the Cu-Sn-Ni-Zn-Ti-Y alloy prepared by this invention exhibits high tensile strength and good electrical conductivity, improving the overall performance of Cu-Sn alloys. Cold rolling deformation causes severe plastic deformation in the alloy, increasing its strength. The addition of rare earth element Y promotes the recrystallization process, forming fine recrystallized grains, and also promotes the precipitation of Cu4Ti phase during aging, further enhancing the alloy's strength. The precipitation of Cu4Ti phase reduces the supersaturation of Ti in the matrix, weakens the scattering effect of the matrix on electrons, and improves the alloy's electrical conductivity. In summary, the rare earth copper-tin alloy prepared by this invention possesses excellent comprehensive properties such as high strength and high electrical conductivity.
[0107] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Therefore, all equivalent changes or modifications made to the structure, features and principles described in the claims of the present invention should be included within the scope of the present invention.
Claims
1. A method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy, characterized in that, Includes the following steps: Step S1, Ingredient preparation: Ingredient preparation is carried out according to the composition of the alloy raw materials. By weight percentage, the composition of the alloy raw materials is: Sn: 1.8~2.1%, Ni: 0.8~1.0%, Zn: 0.4~0.6%, Ti: 0.2~0.3%, rare earth element Y: 0.1~0.2%, and the balance is Cu; Step S2, Preparation of intermediate alloy: Copper and titanium are smelted in a furnace and naturally cooled to obtain Cu-45%Ti intermediate alloy for later use; Step S3: Melting, casting and peeling; The Cu-45%Ti master alloy and Sn, Ni, Zn, Y and the balance Cu are melted in a furnace to obtain an alloy melt; The alloy melt is poured into a sand mold and cooled to obtain an alloy ingot; Step S4, hot extrusion: The alloy ingot obtained in step S3 is heated to 960°C and held for 2 hours, and then hot extruded into bars with an extrusion ratio of 5~10:
1. Step S5, Solution treatment: The bar obtained in step S4 is subjected to solution treatment. The solution treatment involves heating the alloy to 950°C, holding it at that temperature for 2 hours, and then water quenching it. Step S6, cold rolling: The alloy sample obtained in step S5 is subjected to cold rolling deformation, and the deformation amount of the cold rolling treatment is 60%; Step S7, double aging treatment: The alloy sample after cold rolling in step S6 is subjected to double aging treatment at 400~550℃ for 10~240min. After the alloy sample is cooled, it is subjected to double aging treatment at the same temperature and time.
2. The method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy according to claim 1, characterized in that, In step S2, the melting conditions are: evacuating to a furnace pressure of 5 × 10⁻⁶. 2 Pa, then argon gas is introduced into the furnace until the pressure inside the furnace is 0.05 MPa, and the furnace is heated to 1100℃ and smelted for 0.5~1 h.
3. The method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy according to claim 1, characterized in that, In step S3, the melting conditions are: evacuating to a furnace pressure of 5 × 10⁻⁶. 2 Pa, then argon gas was introduced into the furnace until the pressure inside the furnace was 0.05 MPa, the melting temperature was 1200℃, and the melting time was 1 hour.
4. The method for preparing a high-strength, high-conductivity rare-earth copper-tin alloy according to claim 1, characterized in that, Before step S4, the riser and surface oxide scale of the alloy ingot obtained by demolding are removed.
Citation Information
Patent Citations
High-temperature softening resistant Cu-Ni-Sn series high-strength and high-elasticity copper alloy and preparation method thereof
CN114086027A
Ultra-high strengthen, high-conductivity CuNiSi series elastic copper alloy and method for preparing same
CN101333610A